Irrational acts: Maternal death, women’s agency, and the obligation to care in Uganda - Boyd, Lydia (PubMed, 2024)
Following the recommendation of the WHO in the mid-2000s, the Ugandan government banned traditional birth attendants (TBAs) and encouraged all women to give birth in biomedical clinics. Yet in rural Luuka district, about half of women still give birth at home or with the assistance of lay providers. This article examines women's healthcare behavior to better understand decisions that are characterized as irrational by officials, in particular women's choices to delay care, move between providers, and defer health decisions to others. Building on anthropological interest in the relationality of care, this article explores how women compel the care of others, especially under conditions of healthcare scarcity and in contexts outside clinical settings. A focus on the gendered nature of kin-based care provides insight into how acts often characterized as irrational can be modes of action for women in ways that exceed a policy focus on healthcare choice and autonomy.